solve the following question
Let us solve the following differential equation "\\frac{dy}{dx}+3y=3x^2e^{-x}." For this let us multply both parts by "e^{3x}:" "e^{3x}\\frac{dy}{dx}+3e^{3x}y=3x^2e^{-x}e^{3x}." It follows that "(e^{3x}y)'=3x^2e^{2x}." Then "e^{3x}y=3\\int x^2e^{2x}dx=|u=x^2,dv=e^{2x}dx,du=2xdx, v=\\frac{1}{2}e^{2x}|=\\frac{3}{2}x^2e^{2x}-3\\int xe^{2x}dx=|u=x,dv=e^{2x},du=dx,v=\\frac{1}{2}e^{2x}|=\\frac{3}{2}x^2e^{2x}-\\frac{3}{2}xe^{2x}+\\frac{3}{2}\\int e^{2x}dx=\\frac{3}{2}x^2e^{2x}-\\frac{3}{2}xe^{2x}+\\frac{3}{4}e^{2x}+C."
It follows that the general solution is "y=e^{-3x}(\\frac{3}{2}x^2e^{2x}-\\frac{3}{2}xe^{2x}+\\frac{3}{4}e^{2x}+C)=\\frac{3}{2}x^2e^{-x}-\\frac{3}{2}xe^{-x}+\\frac{3}{4}e^{-x}+Ce^{-3x} ."
Comments
Leave a comment